Analisis Implementasi Kebijakan Dalam Pemberdayaan Masyarakat Melalui Program Bank Sampah Merah Delima Rw 006 Kelapa Gading Timur Jakarta Utara - Bagus Raul Krishnawan; Tuswoyo Tuswoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The background of this research is the success of anorganic waste management on limited land in RW 006 of Kelapa Gading Timur, North Jakarta, in contrast to other areas which are constrained by limited land to run a waste bank. The objectives of this study are: 1) to describe and analyze the implementation of community empowerment through the 'Merah Delima Waste Bank' program in RW 006 of Kelapa Gading Timur, North Jakarta; 2) to describe the factors that influence the implementation of community empowerment through the 'Merah Delima Waste Bank' program in RW 006 of Kelapa Gading Timur, North Jakarta; and 3) to analyze and describe solutions to the factors that hinder the implementation of community empowerment through the 'Merah Delima Waste Bank' program in RW 006 of Kelapa Gading Timur, North Jakarta. This research was conducted using a descriptive research method and qualitative approach, where data were collected through observation, interviews, and documentation. The data obtained were analyzed at the stages of data collection, data reduction, data presentation, and conclusion drawing. The results show that the implementation of community empowerment through the 'Merah Delima Waste Bank' program in RW 006 of Kelapa Gading Timur, North Jakarta has been very good, where there are two programs run by the ‘Merah Delima Waste Bank’, namely the waste savings program and the waste management training program. However, in terms of disposition, there has been no incentive in the form of awards given to implementers as support for their achievements. Efforts that can be made to further support this program are to provide land for the Merah Delima Waste Bank so that in the future it can be more effective and efficient in dealing with waste problems, increase training in waste processing crafts so that the results are more diverse, and pick up sorted waste at residents’ houses, places of business and other sources where the residents are still reluctant to leave their residence after the Covid- 19 pandemic.